2020
DOI: 10.1101/2020.03.02.974303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus Small Tumor Antigen Activates Matrix Metallopeptidase-9 Gene Expression for Cell Migration and Invasion

Abstract: 46Merkel cell polyomavirus (MCV) small T antigen (sT) is the main oncoprotein for the 47 development of Merkel cell carcinoma (MCC). MCC is a rare, clinically aggressive 48 neuroendocrine tumor of the skin with a high propensity for local, regional, and distant 49 spread. The expression of matrix metalloproteinase (MMP)-9 has been implicated as 50 playing an important role in cell invasion and metastasis in many human cancers. 51Previously, MCV sT has been shown to increase the cell migration and invasiveness … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
0
0
Order By: Relevance
“…We observed that cells expressing sT in combination with either LT or LTtr exhibited a notable increase in mRNA expression of genes associated with chemotaxis, response to tumor necrosis factor (TNF), and NF-κB signaling. In addition, as reported previously, we found that the presence of sT affects genes associated with angiogenesis and cell adhesion [37][38][39]. Our study further revealed that LT and LTtr disrupt these biological processes similarly.…”
Section: Resultssupporting
confidence: 89%
“…We observed that cells expressing sT in combination with either LT or LTtr exhibited a notable increase in mRNA expression of genes associated with chemotaxis, response to tumor necrosis factor (TNF), and NF-κB signaling. In addition, as reported previously, we found that the presence of sT affects genes associated with angiogenesis and cell adhesion [37][38][39]. Our study further revealed that LT and LTtr disrupt these biological processes similarly.…”
Section: Resultssupporting
confidence: 89%